Features of somatic pathology with psoriasis in the conditions of the Aral Sea region - Z. I. Akhmedzhanova; G. U. Zhanabayeva; K. A. Muldabekova (Лечащий Врач, 2023)
Despite the large number of studies in the world, the peculiarities of the course of psoriasis remain relevant. In the conditions of the Aral Sea region they are especially in demand due to the great chronicity of the process and increased percentage of disability among this category of patients. The analysis of clinical forms, seasonality of exacerbations, concomitant pathology in patients with psoriasis living in the Aral Sea region is carried out in this article based on the observation and data analysis of 135 patients who received hospital treatment in the Republican CVD, Nukus, Republic of Karakalpakstan. The age of the patients ranged from 15 to 70 years old. It was found that progressive stage of psoriasis was registered in 90% of patients, in 10% of patients – stationary stage. Affection of nail plateswas observed in 16% of patients with psoriasis. According to clinical form the vulgar form was revealed in 89% of patients, arthropathic – in 34% of patients, palm plantar form – in 3%, exudative – in 1.5%, seborrheic – in 1.5%, erythroderma – in 6%. Concomitant somatic pathology was detected in 66% of patients. In the structure of somatic pathology of psoriasis patients in the general group the diseases of digestive organs and bone system prevail, pathology of cardiovascular system is revealed to a lesser degree. Cardiovascular system pathology increased up to 36% in the older group. In men there were more often concomitant diseases of bone system in 25% of cases, of digestive organs in 24%, of cardiovascular system in 9%. In women, concomitant diseases of the digestive organs were more frequent in 19% of cases, of the endocrine system in 3%, and of the genitourinary system in 7%. Frequent exacerbation of psoriasis is characteristic for mixed type 44%. Psoriasis is a systemic disease, the course of which is influenced by disturbances in all body systems. The data we obtained revealed a large percentage of concomitant pathology in patients with psoriasis living in the Aral Sea region, which dictates the need to review the therapy options for these patients, taking into account the concomitant pathology and personalization of treatment.